Program One Day One Egg Sebagai Strategi Pemenuhan Kebutuhan Protein Harian Anak untuk Mengurangi Angka Stunting di Desa Jetis, Kecamatan Bandungan, Kabupaten Semarang, Jawa Tengah - Insani, Galuh Adi; Suprapto, Maulina Eril; Nugroho, Khairina Paramesti; Widriati, Rendra Nandira (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Stunting is a multifaceted and urgent issue in Indonesia. The impact of stunting extends beyond health and is also detrimental to the potential of human resources, therefore compromising the quality of future generations. Stunting is characterized by retardation in the growth of children caused by insufficient nutrition during the first 1000 days of life. Numerous food supplementation initiatives have been implemented to reduce the prevalence of stunting, including the "One Day One Egg" campaign in Desa Jetis, Kecamatan Bandungan. The primary objective of this program is to enhance the understanding of posyandu cadres on the significance of incorporating one egg into their daily diet to meet the protein requirements of a child. The program was conducted using a pre-test, material presentation, and post-test to assess the improvement in the knowledge of the target participants. The study findings indicate a substantial rise in post-test scores, by an average gain of 12.73 points, when compared to pre-test grades. The efficacy of the "One Day One Egg" initiative in enhancing the awareness of target participants on the significance of protein consumption for the prevention of stunting has been successfully demonstrated. It is anticipated that this program will be implemented in everyday life to reduce the prevalence of stunting in Desa Jetis.